High prevalence of Schistosoma japonicum by perfusion in naturally exposed water buffalo in a region of the Philippines endemic for human schistosomiasis. - Mario Jiz; Claro Mingala; Zhi-Qiang Fu; Melika Adriatico; Ke Lu; Blanca Jarilla; Marianne Sagliba; Ammabelle Moreno; Sangshin Park; Jiao-Jiao Lin; Remigio Olveda; Jonathan D Kurtis; et al. (Public Library of Science (PLoS), 2021)
In the past decade, ecological surveys emphasized rats and dogs as the most significant animal reservoirs for Schistosoma japonicum (S.j) in the Philippines. However, recent studies demonstrated 51-91% prevalence of schistosomiasis among water buffalo using qPCR in the Sj endemic regions in the Philippines. In order to resolve the inconsistency of reported surveys regarding Sj endemicity among carabao, a domestic water buffalo that is the most important draught animal, we introduced 42 schistosome negative water buffalo to Macanip, Jaro municipality, Leyte, the Philippines, a subsistence rice-farming village that has been the focus of schistosomiasis japonica studies of our group for the past 20 years. We conducted perfusion to the remaining 34 buffalo that survived 10 months of nature exposure and Typhoon Haiyan. Thirty-three water buffalo were found to be positive with at least 1 pair of worms from the mesenteric vein. The infection rate is 97%, with the worm burden of 94 (95% confidence interval, 49-138 worms) worms. To our knowledge, this is the first report about S. japonicum worm burden in naturally infected water buffalo in the Philippines. The fact that with less than one-year of exposure, in this human schistosomiasis endemic area, only 1 out of 34 water buffalo was uninfected is striking. Urgent attention is needed for a cost-effective technique for monitoring Sj infection in animals and humans. Meanwhile, intervention implementation, including water buffalo treatment and vaccination, should be taken into consideration.